(untitled) (Balneo and PRM Research Journal, 2024)
Abstract: Vitamin D is essential in determining bone and muscle health. Vitamin D deficiency (VDD) produces secondary hyperparathyroidism, loss of bone quality and mass, mineralization effects and fractures, myopathy, and falls. The avascular necrosis (AVN) of the femoral head pathophysiology is still unclear and can be considered a vascular bone disease. Our paper aimed to evaluate the etiology of AVN in a young male with bilateral femoral neck damage who required bilateral arthroplasty. Method: We present the case of a 46-year-old male patient with VDD and bilateral total hip arthroplasty for osteoarthritis secondary to AVN of the femoral head. After complete hormonal, biological, and imaging evaluations, the diagnosis of primary hyperparathyroidism was not supported; the improvement of vitamin D deficiency after eight months of treatment clarified the diagnosis: hyperparathyroidism secondary to vitamin D deficiency. Results: Supplementation with 4000 IU of vitamin D improved the patient’s response to specific rehabilitation methods. Conclusions: Severe vitamin D deficiency can secondarily affect the structure of the femoral head through secondary hyperparathyroidism, producing AVN, but only osteopenia was obtained on DXA evaluation. VDD can be an important etiological factor in the occurrence of AVN, and its correction can improve the evolution of the disease, improving the reabilitation of these patients. Keywords: avascular necrosis, secondary hyperparathyroidism, vitamin D deficiency, rehabilitation